Afrika - Atlantik - Amerika Sklaverei und Sklavenhandel in Afrika, auf dem Atlantik und in den Amerikas sowie in Europa - Zeuske, Michael (Dependency and Slavery Studies, 2022)
This book centers on the Africa-Atlantic-Americas system and its relationship to the complex of Atlantic slavery, regimes of slavery on land in Africa and America, enslavement and transport over land and water, and the slave trade in the Atlantic. The volume pays special attention to the South-South component as an essential factor in slavery and on the significance of the AAA system in the history of modernity and capitalism.